Solar energy management for poverty alleviation and income generating activities - Mohiuddin, A. K. M. (IIUM Press, 2011)
Conventional modes of power besides running out are also aggravating the environment. New and renewable forms of energy are the need of the day. The abundance, inexhaustibility and non-polluting nature of the sun's energy to the earth, have made solar energy the right supplement for conventional energy sources, which are getting scarce and exhausted. For proper management of solar energy, private sector must come foward to take the initiative. A tripartite management system is proposed in this chapter. The first party of the management system is the supplier/manufacturer of the different components of the solar power system and is responsible to extend proper training to the personnel of the third party. The second party of the management system is the bank who will finance the solar power projects. The third party of the management system is an NGO who has got its network in rural areas and will be responsible to carry out all the installation work with the help of the first party. They will also be responsible to collect the loan installments/rents from the end-users. The tripartite management with their concerted efforts can make a successful solar power project in remote rural areas.